2015
DOI: 10.5935/medicalexpress.2015.04.01
|View full text |Cite
|
Sign up to set email alerts
|

The effect of gait training and exercise programs on gait and balance in post-stroke patients

Abstract: The aim of this review is to evaluate studies about gait training and exercise interventions applied to patients following chronic stroke on gait and balance. The studies included in this review were random clinical trials, including only chronic post-stroke individuals that evaluated gait and balance outcomes and with a PEDro scale score ≥ 7.0. Eight studies were selected. The results suggest gait and balance will only be affected in chronic post-stroke patients if training sessions last at least 30 minutes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
4
0
2
Order By: Relevance
“…Therefore, shorter step time stabilizes fixation of the opposite leg, provides a strong stimulus to improve function of the opposite leg, and decreases cycle time and double support time, ultimately improving the quality of gait. Mochizuki et al 44 observed changes in gait velocity and step length depending on balance, and reported that this was related to improvements in gait ability and fall risk. In particular, in stroke patients, various surfaces exercise affects limb coordination and gait ability by improving static and dynamic balance, and this ultimately increases physical stability and improves the quality of gait.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, shorter step time stabilizes fixation of the opposite leg, provides a strong stimulus to improve function of the opposite leg, and decreases cycle time and double support time, ultimately improving the quality of gait. Mochizuki et al 44 observed changes in gait velocity and step length depending on balance, and reported that this was related to improvements in gait ability and fall risk. In particular, in stroke patients, various surfaces exercise affects limb coordination and gait ability by improving static and dynamic balance, and this ultimately increases physical stability and improves the quality of gait.…”
Section: Discussionmentioning
confidence: 99%
“… 10 According to previous studies, gait training decreased the risk of falling and increased the gait speed in chronic stroke patients. 11 Loaded gait training increased the dynamic stability and functional performance of stroke patients. 12 Limb-loading during knee flexion and extension movements on the ground also increased electromyography (EMG) activity of the RF muscle, 13 and limb-loaded walking increased RF muscle activity during walking on a treadmill in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…The degeneration of such systems due to aging is associated to lower functional performance and to higher risk of falling, thus possibly making these individuals dependent on others. However, many different treatments have been used; among them, conventional physical therapy can be highlighted, featuring many intervention techniques to reduce the aging effects, such as the combination of balance and strength training [9], gait training [10] and others, thus helping these people to return to their daily life activities with better quality.…”
Section: Introductionmentioning
confidence: 99%